Analyser la mise en œuvre des politiques d’éducation compensatoire au prisme de la sociologie des organisations - Julia Napoli (Recherches en Éducation)
Compensatory education is defined as a policy aimed at reducing educational inequalities through a principle of equity. To date, research on compensatory education has demonstrated the failure of these policies and are mainly focused on policy design and their effects or in teaching practices. We have chosen to focus our research work on an analysis of the implementation of compensatory education policies. In this article, we try to demonstrate how the approach of the sociology of organizations is relevant in this case. The chosen sociological point of view will allow us to understand the structure of actors' relationships and its impact on the implementation of compensatory education at the intermediate and local level. Our first results in the canton of Geneva show no structure or complex structures of relations according to the level of the actors, due in particular to the absence of meaning of the policy.